Upaya Meningkatkan Minat dan Kemampuan Kognitif Siswa SMK Melalui Waze Apps - Hijrah Syahputra (PEDAGOGIKA, 2020)
The aim research is icreased instruction quality and utilized Waze software on Mekanika Teknik subject matter amongst SMK Negeri 3 Gorontalo, X TP-2 grade. This research used classroom action research method, consisting of two cycles. Each cycles: (1) plan; (2) implement; (3) act observe; and (4) reflect. This research utilized Waze software in discovery learning strategy. Data collected from observation, questionnaire, and paper test. This research has revealed that, there were enhancement in the learning interest and cognitive skill of student. Based on these findings, it was therefore recommended that Mekanika Teknik Teacher should be encouraged to use Waze software on internet for effective instruction of Mekanika Teknik subject matter.